A combination of midlife diabetes mellitus and the apolipoprotein E ε4 allele increase risk for cognitive decline - Lee, Boung Chul; Choe, Young Min; Suh, Guk-Hee; Choi, Ihn-Geun; Lee, Jun Ho; Kim, Hyun Soo; Hwang, Jaeuk; Yi, Dahyun; Kim, Jee Wook (Frontiers in Aging Neuroscience, 2022)
Background: It has been suggested that diabetes mellitus (DM) and the apolipoprotein E (APOE) ε4 allele (APOE4) increase the risk for Alzheimer’s disease (AD) and cognitive decline. However, the evidence is sparse. We explored whether APOE4 status modulated the effects of midlife and late-life DM on global cognition of non-demented older adults. Methods: In all, 176 non-demented adults (age 65 to 90 years) were enrolled. All the participants underwent comprehensive clinical assessments including midlife and late-life DM evaluation and APOE genotyping. The global cognitive performance index was assessed by the total score (TS) of the Consortium to Establish a Registry for Alzheimer’s Disease neuropsychological battery. Results: We found a significant midlife DM × APOE4 interaction effect on the global cognitive performance. Subgroup analyses indicated that an association between midlife DM and decreased global cognitive performance was apparent only in older adults who were APOE4-positive, and not in those with APOE4-negative. Conclusions: Our findings from non-demented older adults suggest that midlife DM increases the risk for AD and cognitive decline, and this risk is modulated by APOE4 status. To prevent AD and cognitive decline, physicians should check for the possible coexistence of midlife DM and APOE4-positive status.